Comparative Study of the Histopathological Changes of Liver and Lung of Two Lines of laying Chickens Experimentally Infected by Ascaridia galli - Wurood Saadoon Al-Alwani; howaida hamle abed (مجلة الانبار للعلوم البيطرية, 2024)
This work aimed to determine the effect of A. galli on the histological changes in the liver and lung of two distinct lines of laying chickens and study the resistance of each line. In this study, fifty laying hens 8 weeks of age were used, (25 of which were Lohmann brown-classic and 25 of which were Lohmann lsl-lite). Each line was divided into two groups: the infected group (N=15) these chickens were infected with a single dose of 500 embryonated eggs through oral inoculation, and the second group control group (N=10) was given normal saline. After 8 weeks the chickens were killed to examination the histological changes. The results showed a histopathological lesion of the liver of the Lohmann brown-classic infected group showed fatty degeneration, blood vessels congestion and the fibrin and inflammatory cells in the lumina of the dilated veins these inflammatory cell infiltrations include eosinophil, while Lohmann lsl-lite showed congestion of blood vessels, as well as lymphocyte infiltration of the inflammatory cells. The lung of Lohmann brown-classic showed congestion in inflammatory cell blood vessels and infiltration with alveolar congestion and eosinophils inflammation and necrotic patches, whereas histopathological changes of the lung of Lohmann lsl-lite showed eosinophils proliferation within an alveolar wall, deterioration of their lumina as a result of haemorrhage. While the control group of two-line showed normal liver and lung. Concluded that the A. galli had an effect on the histological structure of the liver and lung, additionally, Lohmann lsl-lite was more affected and less resistant compare to Lohmann brown-classic. [AJVS 2024; 17(2.000): 40-45]